PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMENPADA PT JUMBO SWALAYAN MANADO - OHY, VELNAWATY K.L.; Kalangi, Johny A. F.; Rogahang, Joula J. (JURNAL ADMINISTRASI BISNIS, 2017)
Customer satisfaction is also one of the important things in a marketing. When a customer feels satisfied with a product or service, then customers generally will continue to buy and use it. And indirectly he will promote by telling others about his experience of the quality of the products or services he has used. Conversely, if customers are not satisfied then tend to move to another place. This study aims to determine and prove how much influence the quality of service to customer satisfaction at PT Jumbo Swalayan Manado. The population in this study are consumers who shop at Jumbo Self-service. Samples taken by 50 respondents by using non prpbability sampling technique with accidental sampling approach, that is sampling technique based on chance, that anyone who happened to meet with the researcher can be used as sample if considered suitable. One of the factors that determine the level of success and quality of the company is the ability of the company in providing services to customers. Every business competes to produce the best service quality for its consumers. According to the Parasuraman (in Rambat 2013: 216) the quality of services can be defined as how far the difference between reality and consumer expectations for the services they receive. Meanwhile, according to Tjiptono (2007) the quality of service as an effort to meet the needs and desires of consumers and the accuracy of delivery in the balance of consumer expectations. Based on the results of research and data analysis, the regression equation is generated ie, with the value of determination. This means that consumer satisfaction is influenced by the independent variable (service quality) consisting of reliability, responsiveness, assurance, empathy, tangible,, while the rest is heard by variable. Beyond this study is quite small, then the next research is suggested to examine the variables that exist outside the study but have a proportion that the quality of service has a positive and significant impact on customer satisfaction at PT Jumbo Swalayan Manado. Given the greater quality of service impact on customer satisfaction is expected to more companies improve services to create loyal customers. Keywords: Service Quality, Consumer Satisfaction